Русифікаційна політика й ідеологія Російської імперії та національне самосприйняття українців (XIX — початок XX ст.) - Крижановська, О.О. (Проблеми історії України ХІХ – початку ХХ ст., 2019)
Статтю присвячено особливостям менталітету та національного самосприйняття українців у ХІХ ст., коли значна частина українських земель входила до складу Російської імперії й вважалася її споконвічними та невід’ємними територіями. В умовах активної та всебічної русифікаторської внутрішньої політики російського самодержавства на українських територіях імперії частина українців поступово асимілювалася, переймаючи притаманні російському народу риси, спосіб життя, звичаї та традиції. Однак у цей же час активно розвивались вітчизняні історичні студії. Вітчизняні учені-історики всебічно та ґрунтовно досліджували минуле, побут, звичаї та традиції українського народу, завдяки чому українська історія стала виокремлюватися з загальноросійської імперської історії. Крім того, на увагу вдумливих дослідників заслуговує широке коло особових джерел ХІХ — початку ХХ ст.: щоденники, записки, мемуари та епістолярії. Ці джерела засвідчують, що український народ ревно зберігав і передавав із покоління в покоління власні та характерні тільки для нього менталітет, риси характеру та спосіб життя. The article is sanctified to the features of mentality and national consciousness of Ukrainians in the period of ХІХ of century, when considerable part of Ukrainian earth entered in the complement of the Russian empire and were considered her by native and inalienable territories. In the conditions of active and all-round rusificatin domestic policy of Russian autocracy on Ukrainian territories of empire part of Ukrainians assimilated gradually, adopting inherent to the Russian people lines, way of life, customs and traditions. However in the same time home historical studios developed actively. Home scientists-historians all-round and thoroughly investigated the past, way of life, customs and traditions of the Ukrainian people, due to what Ukrainian history began to be distinguished from all-Russian imperial history. In addition, attention of serious researchers is deserved by the wide circle of the personal sources of ХІХ — to beginning of ХХ of century are diaries, messages, memoirs and epistolary. These sources certify that in the Ukrainian people jealously kept and passed from a generation in generations own and characteristic only for him mentality, character traits and way of life. Sources testify however, that in the Ukrainian people in the same time kept and passed from a generation in generations own and characteristic only for him mentality, character traits and way of life.